The Role of the Family Environment in Fostering a Reading Literacy Culture among Elementary School Children - Aisyah; Nurjanah, Nunuy; Ulug'bek, Xoduk (CV. Goresan Pena, 2025)
Literacy is not only about reading and writing skills, but also includes the ability to understand and use information critically, so that a culture of reading literacy is critical in developing children's knowledge and insight. However, literacy conditions in Indonesia are still low. Therefore, the family environment plays a vital role as the primary foundation in fostering a culture of reading literacy in elementary school children through role models, support, and provision of facilities that support reading activities at home. The study aimed to identify the most influential family factors in building a literacy culture and formulate practical strategies that parents can apply to create a home environment conducive to developing elementary school children's literacy. This study uses a qualitative descriptive method. Data was collected through documentation studies of relevant literature to build a conceptual framework and an in-depth understanding of the topic. Data analysis was carried out through three main stages: data reduction, data presentation, and drawing and verifying conclusions. The study results showed that the family environment plays a vital role in fostering a culture of reading literacy in elementary school children through role models, emotional support, and adequate reading facilities. The active involvement of parents in children's literacy activities has been shown to increase interest in and improve reading habits from an early age.